O'Brien, Aloysius 6. Interview about the generations of O'Brien family in the farm and the sale of products from the farm - Shawyer; Jo (1992)
The first part of the conversation concentrates on the generations of O'Brien family who are the owers of the farm. In the second part, Aloysius talked about the sale of the products in the farm. "00:00-05:00 owners of generations of the farm; John O’Brien; hometown in Ireland; 05:00 – 10:00 John O’Brien; Timothy; 10:00-15:00 Patrick O’Brien; 15:00- 20:00 Michael O’Brien; Dennis O’Brien 20:00 -25:00 Michael’ other sons; Dennis 25:00- 30:00 Dennis’ children; three brothers 30:00 -35:00 products in the farm; the truck system 35:00 - 40:00 loyalties in trade; preparation of vegetables; sacks; barrels; turnips; apples 40:00 – 44:53 growing turnips; products selling; merchant; "